2019
DOI: 10.1089/neu.2018.5889
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation with Resting-State Network Targeting for Treatment-Resistant Depression in Traumatic Brain Injury: A Randomized, Controlled, Double-Blinded Pilot Study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has demonstrated antidepressant efficacy but has limited evidence in depression associated with traumatic brain injury (TBI). Here, we investigate the use of rTMS targeted with individualized resting-state network mapping (RSNM) of dorsal attention network (DAN) and default mode network (DMN) in subjects with treatment-resistant depression associated with concussive or moderate TBI. The planned sample size was 50 with first interim analysis planned at 20, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 70 publications
1
113
0
Order By: Relevance
“…Research efforts over the past 2 decades have aimed to improve the efficacy and consistency of treatment effects across individuals. While optimal stimulation parameters and dosing are important, one major source of interindividual heterogeneity in treatment outcomes arises from variation in the stimulated site across the spatial extent of the DLPFC (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Therapeutic Brain Stimulation For Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research efforts over the past 2 decades have aimed to improve the efficacy and consistency of treatment effects across individuals. While optimal stimulation parameters and dosing are important, one major source of interindividual heterogeneity in treatment outcomes arises from variation in the stimulated site across the spatial extent of the DLPFC (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Therapeutic Brain Stimulation For Depressionmentioning
confidence: 99%
“…Many have suggested that rTMS might be improved by personalizing the stimulation site based on individual differences in connectivity (5,6,9,11,12,16,(92)(93)(94)(95)(96). Recent work demonstrates that SGC FC shows considerable interindividual variation across the spatial extent of the DLPFC (5,92,96).…”
Section: Targeting Tms Based On Individualized Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that abnormal brain regions in the DAN were associated with cognitive impairment in MCI patients (Tao et al, 2017a). Electrical or magnetic stimulation of the DAN core brain areas has been shown to improve attention in patients with MCI (Anderkova et al, 2018; Siddiqi et al, 2019). Aerobic exercise increases the frontal gray matter, including the anterior cingulate cortex, the supplemental motor area, middle frontal gyrus, superior frontal gyrus, and the superior and inferior parietal lobules, and its functional connections, which may be involved in top-down attentional processes (Colcombe et al, 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Methylphenidate improves mental processing speed and attentiveness in adults with postacute attention deficit following TBI Specific types of repetitive transcranial magnetic stimulation alleviate headache and depression in adults with chronic concussive/“mild”‐to‐moderate TBI Sustained‐release melatonin 2 hours before bedtime modestly improves sleep quality, anxiety, and fatigue in chronic TBI patients with insomnia .…”
Section: Examples Of Domain‐specific Candidate Treatments For Tbimentioning
confidence: 99%